Metatranscriptomics reveals climate change effects on the rhizosphere microbiomes in European grassland. (November 2019) - Bei, Qicheng; Moser, Gerald; Wu, Xiaohong; Müller, Christoph; Liesack, Werner
Abstract: Although the fertilizing effect of elevated atmospheric CO2 on plant growth is well established, its impact on the structure and activity of below-ground biota remains elusive. Here, we used metatranscriptomics to assess possible effects of moderately elevated CO2 (eCO2 ) on grassland rhizosphere microbiomes at the Giessen free-air CO2 enrichment (GiFACE) site in August of 2015 and 2017. Since its launch in 1998, the GiFACE atmospheric CO2 concentration has been maintained at 20% higher than ambient air levels, thereby suggesting a realistic ecosystem response to eCO2 . Metatranscriptomics revealed significant eCO2 effects on the composition and activity of the grassland microbiomes in 2015, but not in 2017. The summer of 2015 was characterized by prolonged heat waves, while the summer temperature in 2017 was close to the long-term average. In August 2015, rRNA and mRNA abundances of Eukarya relative to Bacteria were significantly decreased in eCO2 plots, in both rhizosphere soil and root-associated microbiomes. On SSU rRNA level, the significant increase in bacterial abundance was primarily related to an enrichment of Actinobacteria and Proteobacteria and, most pronounced, a decline in Fungi . In addition, we observed an enrichment of Acidobacteria, Bacteroidetes, Chloroflexi, and Planctomycetes and, among Eukarya, a decline in Amoebozoa, SAR group, and Metazoa . The decrease in soil fungal activity was confirmed by RT-qPCR of 18S rRNA; in good agreement with a significant decrease in fungal mRNA involved in oxidative phosphorylation (rhizosphere soil), and in folding, sorting and degradation (root-associated). Among Fungi, the relative abundance of most groups (e.g., Agari co mycetes [soil] and Leotiomycetes [roots]) decreased, but that of the Glomeromycetes (both compartments) increased. Functional analysis of root mRNA suggests that the production of plant secondary metabolites was increased in the summer of 2015. These may have acted as an effective combat strategy against phytopathogenic fungi, such as Leotiomycetes . In conclusion, our metatranscriptomic study suggests that a near-future level of eCO2 combined with prolonged heat waves may have a significant impact on the interactome between rhizosphere microbiomes and plant roots in European grassland; with a primary effect on fungal activity. Highlights: The impact of elevated atmospheric CO2 (eCO2 ) on the rhizobiota was assessed. Metatranscriptomics revealed major eCO2 effects in the extreme summer of 2015. No significant eCO2 effects were observed in the normal summer of 2017. In 2015, RNA abundance of Eukarya relative to Bacteria was significantly decreased. An altered root-microbe interactome particularly affected the fungal activity.